Raspberry Pi-based home security monitoring system - Mahyan Fariza Binti; Lit Asrani Bin; Satu Nglai Anak; Banyah Mark Sydney Anak; Gumis Mcirvine Igoh Ak (E3S Web of Conferences, 2024)
The era of technology has opened space to facilitate daily tasks. Security cameras have nowadays become a necessity for every expert’s safety environment. A buzzer, PIR sensor, PI camera, and Raspberry Pi are used to create home security systems. The PIR sensor detects motion, the PI camera snaps an image, and the buzzer beeps. A notification will be delivered immediately to the owner’s Telegram account when the camera captures the person’s face and enables the posting of live video of that moment. It enables the user to record the incidents that happen at home. The purpose of developing the Telegram application is mainly to provide the owner with an Android application because nowadays society is more dependent on mobile technology. PIR sensors will be active when they detect people or animals, but they will deactivate when they detect breezes. As a result, the PI Camera will only record images of things like people and animals, not the wind. The PIR sensor, PI camera, and buzzer will all have a linear relationship to one another. When the PIR sensor is turned on, the PI camera and buzzer will also turn on, and vice versa.